Penapisan Profil Kolesterol Total dan HDL dalam Rangka Peningkatan Upaya Preventif terhadap Penyakit Kardiovaskular di SMP Kalam Kudus 2, Jakarta - Jeffrey Jeffrey; Alexander Halim Santoso; Edwin Destra; Andrew Philo; Steven Hizkia Lucius; Ryan Daffano Putra Mahendri (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2025)
An imbalance between total cholesterol and HDL levels is a significant risk factor for cardiovascular disease that often goes unrecognized by individuals. Excessive calorie intake from high-fat and high-sugar foods is the primary contributor to dyslipidemia. Lipid profile screening plays a crucial role in early detection and serves as an opportunity to educate individuals about healthy lifestyle choices. In this community screening activity, 91 adult participants underwent capillary blood testing using a Point-of-Care Testing (POCT) device. The parameters assessed included total cholesterol and HDL levels. Educational materials were provided in the form of a leaflet emphasizing the effects of excessive caloric consumption on lipid imbalance and cardiovascular risk. A total of 52 participants (57.1%) were found to have elevated total cholesterol levels, and only 27 participants (29.7%) had HDL levels within the normal range. The mean total cholesterol level was 203.6 ± 44.0 mg/dL, while the mean HDL level was 51.8 ± 17.9 mg/dL. These findings indicate that most participants had an unfavorable lipid profile, highlighting the urgent need for lifestyle interventions. Measuring total cholesterol and HDL levels proved effective in identifying individuals at risk of dyslipidemia. Moreover, educating participants about high-calorie dietary patterns is an essential preventive measure to increase public awareness, promote lipid balance, and reduce the risk of cardiovascular complications at an early stage.